Development of regional and communicative skills when learning German in Kryvyi Rih - Valentyna A. Karpiuk (Academy of Cognitive and Natural Sciences, 2020)
The article considers the problem of the local lore competence development of foreign language faculties' students as an integral component of communicative competence with usage of local lore information and facts about the country of the language being studied, ways of its solution and corresponding methods for their use are proposed. The relevance of using facts about German traces in Kryvyi Rih in the process of learning German in educational institutions is substantiated. The theoretical foundations and results of the research are described. It has been found that increasing the volume of national competence contributes to increased motivation, leads to a more conscious learning of the German language. During the exercises aimed at development the competence, it is important to focus on the differences in the compared concepts' interpretation of the cultures being compared, on the ability to identify the connection between the lexical background and the general content of the text, on the development of thinking in stereotypes, fullfledged communication and the subconscious sense of a language. It is not the content of the local lore material itself that gets particular importance, but the fact that such content develops and improves attitudes and competencies, and enables students to discover their abilities. It is stated that the most effective forms of work in the development of local lore and communication competencies can be: search and research work, project, work in tandem, group games using the latest information technologies and internet resources; user search skills on the internet; joint activities with other participants through online resources; using online resources for publications and sharing their professional achievements. That allows and promotes remote working and constant analysis of a language occurance, lay of the land being learned, association relationships are used in a way of comparison with the native language. The study results have been summarized and the contemplations of further studies are defined.